STUDI PEREMAJAAN TANAMAN KELAPA SAWIT DI AREAL LAHAN TANAH MINERAL DAN LAHAN GAMBUT - Gatot Pramuhadi; Muhammad Aji Setiawan; Nenda Fuji Putri Daliesta (The University of Lampung, 2020)
Oil palm trees that are more than 25 years old generally have low productivity of oil palm fruit and will decrease in productivity. For this reason, it is necessary to replant oil palm plants so that their productivity can be maintained high and increased. The aim of this research is to study the technique of replanting oil palm plants in mineral soil areas in the area of Kebun Aek Loba, PT Socfindo, Asahan Regency, North Sumatra Province and in the peatland area of Kebun Mandah Estate, PT Bhumireksa Nusa Sejati, Riau Province. Soil types in the Aek Loba garden area were dominated by mineral soils of the typic hapludult class and made from mother rock tufo toba and young alluvium with a soil pH of 5.5. Mandah Estate plantation area is 100% peat soil with a composition of 74% mature peat (sapric) and 26% medium peat (hemic). Peat is more than 3 meters deep (including very deep peat) and has a crumbly texture so it is easy to erode. The peat soil includes ombrogin peat (formed from large swampy plains), has a high acid content with a pH < 5.5, and has a peat soil density of (1.25 - 1.80) g / cc. Replanting activities in mineral soil areas include ripping, plowing, chipping, holing to planting with a large field capacity (0.04 - 0.72) ha / hour and a total time of completion of work (total field time) of 139.5 hours / ha. Replanting activities in peatland areas include falling, chipping, deboling, holing and planting with a large field capacity (0.06 - 1.25) ha / hour and a total field time of 73.7 hours / ha. Keywords: field capacity, mineral soils, peatlands, replanting, total field time